Internationalization of post-Soviet Economists: Evidence from Central Asia and the Caucasus - Murat Çokgezen; Jale Çokgezen (Journal of Economics and Political Economy, 2014)
After the collapse of socialism, post-Soviet republics reorganized economics curricula, published new textbooks, and trained students and academics in their home countries or in the West. How did these efforts change the quantity and quality of international publications of post-Soviet economists? The results of this study show that the number of international publications increased gradually. These publications usually concern regional issues and are published in low impact journals. The preference of Russian language journals implies that language is a barrier to publish in international journals. Cooperation with Westerners is found to contribute positively to their publication performance.
Keywords: A10; P27; 330; Transition; economics education; Caucasus; Central Asia; Publication performance